Dietary Supplementation With Nonfermentable Fiber Alters the Gut Microbiota and Confers Protection in Murine Models of Sepsis. Issue 5 (May 2017) - Morowitz, Michael J.; Di Caro, Valentina; Pang, Diana; Cummings, Jessica; Firek, Brian; Rogers, Matthew B.; Ranganathan, Sarangarajan; Clark, Robert S. B.; Aneja, Rajesh K.
Abstract : Objectives: Links between microbial alterations and systemic inflammation have been demonstrated in chronic disease, but little is known about these interactions during acute inflammation. This study investigates the effect of dietary supplementation with cellulose, a nonfermentable fiber, on the gut microbiota, inflammatory markers, and survival in two murine models of sepsis. Design: Prospective experimental study. Setting: University laboratory. Subjects: Six-week-old male C57BL/6 wild-type mice. Interventions: Mice were assigned to low-fiber, normal-fiber, or high-fiber diets with or without antibiotics for 2 weeks and then subjected to sepsis by cecal ligation and puncture or endotoxin injection. Fecal samples were collected for microbiota analyses before and after dietary interventions. Measurements and Main Results: Mice that received a high-fiber diet demonstrated increased survival after cecal ligation and puncture relative to mice receiving low-fiber or normal-fiber diets. The survival benefit was associated with decreased serum concentration of pro-inflammatory cytokines, reduced neutrophil infiltration in the lungs, and diminished hepatic inflammation. The high-fiber diet also increased survival after endotoxin injection. Bacterial 16S ribosomal RNA gene sequences from each sample were amplified, sequenced, and analyzed. Fiber supplementation yielded an increase in relative abundance of the genera Akkermansia and Lachnospiraceae, taxa commonly associated with metabolic health. Administration of antibiotics to mice on the high-fiber diet negated the enrichment of Akkermansia species and the survival benefit after cecal ligation and puncture. Conclusion: Dietary supplementation with cellulose offers a microbe-mediated survival advantage in murine models of sepsis. Improved understanding of the link between diet, the microbiota, and systemic illness may yield new therapeutic strategies for patients with sepsis. Abstract : Supplemental Digital Content is available in the text.